2018
DOI: 10.1016/j.ygyno.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy in elderly women with ovarian cancer: Rates of use and effectiveness

Abstract: Careful consideration should be given to older patients prior to undergoing PCS. Survival outcomes were similar for patients with stage IV disease, although NACT was associated with decreased perioperative morbidity compared with PCS. Among women with stage III disease, PCS was associated with improved overall survival, but higher rates of perioperative morbidity and acute care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Furthermore, NACT has been shown to have decreased intraoperative blood losses, is less likely to receive perioperative blood transfusions with decreased number of units received, has earlier times to ambulation and return of intestinal function, and has shorter LOS [28,29,31,32,33,34]. NACT is also associated with significantly fewer intestinal diversions (10.8% vs. 23.3%, p < 0.0001) [35]. NACT is becoming increasingly common in the United States as quality and safety data continues to favor NACT over PCS [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NACT has been shown to have decreased intraoperative blood losses, is less likely to receive perioperative blood transfusions with decreased number of units received, has earlier times to ambulation and return of intestinal function, and has shorter LOS [28,29,31,32,33,34]. NACT is also associated with significantly fewer intestinal diversions (10.8% vs. 23.3%, p < 0.0001) [35]. NACT is becoming increasingly common in the United States as quality and safety data continues to favor NACT over PCS [36].…”
Section: Discussionmentioning
confidence: 99%
“…Summary of major U.S. observational studies is shown in Table 2. When it comes to "real-world practice", the results are heterogeneous across the study populations [6][7][8][9][10][11]. For instance, results from a multicenter retrospective study among the National Cancer Institute designated centers in the United States noted better clinical outcomes in patients treated with pTRS, but higher complete cytoreduction rates in patients treated with NACT.…”
Section: Observational Studies Evaluating Nactmentioning
confidence: 99%
“…The use of NACT has increased annually by 10.3% between 2011 and 2016 compared with an annual increase of 7.9% between 2006 and 2011 [7]. The results of NACT trends in several major U.S. observational studies are displayed in Figure 1 [6][7][8][9][10][11]. Overall, the NACT use has increased significantly in recent years particularly for patients with stage IV disease.…”
Section: Introductionmentioning
confidence: 99%
“…
ObjectiveNeoadjuvant chemotherapy for advanced ovarian cancer is associated with reduced morbidity in the elderly (Meyer et al, 2018). Spontaneous colonic perforation often leads to multisystem organ failure and death (Carter and Durfee, 2007; Rose and Piver, 1995).
…”
mentioning
confidence: 99%